2001
DOI: 10.1001/jama.285.12.1613
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Development, and Behavior in Early Childhood Following Prenatal Cocaine Exposure

Abstract: Among children aged 6 years or younger, there is no convincing evidence that prenatal cocaine exposure is associated with developmental toxic effects that are different in severity, scope, or kind from the sequelae of multiple other risk factors. Many findings once thought to be specific effects of in utero cocaine exposure are correlated with other factors, including prenatal exposure to tobacco, marijuana, or alcohol, and the quality of the child's environment. Further replication is required of preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
239
0
11

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 481 publications
(264 citation statements)
references
References 91 publications
11
239
0
11
Order By: Relevance
“…Not one of seven published studies using parent-report measures of behavior problems have found significant effects of PCE. [3][4][5] In contrast, four of the five studies using teacher-report measures have reported significant findings. [6][7][8][9] However, all were based on the same cohort.…”
mentioning
confidence: 89%
“…Not one of seven published studies using parent-report measures of behavior problems have found significant effects of PCE. [3][4][5] In contrast, four of the five studies using teacher-report measures have reported significant findings. [6][7][8][9] However, all were based on the same cohort.…”
mentioning
confidence: 89%
“…Exposed infants were stigmatized as a biologically doomed underclass. Today, fetal exposure to crack or cocaine is considered no more harmful than exposure to tobacco or alcohol 5 , but criminal prosecution of pregnant women who take such drugs continues.…”
Section: Alarming Precedentsmentioning
confidence: 99%
“…A 2001 review of 36 peer-reviewed articles revealed that in most domains, the neurobiological effects of PCE play a subtle role, with effects no greater than other known teratogens or environmental factors [12]. Associations between PCE and negative developmental outcomes were typically attenuated when models included conditions that commonly co-occur with PCE (e.g., tobacco or alcohol exposure, malnutrition, poor quality of care).…”
Section: Postpartummentioning
confidence: 99%